Economic recovery and growth plan, economic sustainability plan and national development plan (2021-2025): The Nigerian experience under President Muhammadu Buhari - Bassey Ekpenyong Anam; Uno Agbor Ijim; Virginia Emmanuel Ironbar; Abang Pius Otu; Otu Offiong Duke; Maxwell-Borjor Achuk Eba (Cogent Social Sciences, 2024)
Economic policies are drivers of development. The President Muhammadu Buhari-led administration in Nigeria (2015–2023) recognized that the economy is likely to remain on a path of steady and steep decline if nothing is done to change the trajectory of declining economic growth. This concern led to the initiation of the Economic Recovery and Growth Plan. The objective of the paper is to examine the experience of the Nigerian economy with the plan. This is desk research. Data are obtained from secondary sources and analyzed through content analysis. It leverages extant literature and the publication of the National Bureau of Statistics (2017), Budget Office of the Federal Republic of Nigeria (2020), and Nigeria Economic and Sustainability Plan (2020) to discuss the framework and implementation of the Economic Recovery and Growth Plan (ERGP), Economic Sustainability Plan and the National Development Plan, in Nigeria. The results of the content analysis show that certain affect the effective implementation of the economic plan. The challenges include a lack of policy continuity, weak institutions and corporate governance, and inadequate funding of policy goals, among other things. By implication, the contributions of the policies to national development have not been significant. The paper advocates the need for the present administration to support the goals of the National Development Plan, by funding the policy goals and strengthening the administrative framework of the bureaucracy for effective performance and sustainability.